The Effect of Perceived Product Quality and Price on Local Brand Fashion Consumer Satisfaction - Fadhillah, Muhammad Daffa Yafie; Simanjuntak, Megawati (Universitas Mercu Buana, 2024)
Fashion trends in Indonesia have continued to grow rapidly in recent years. This has created an increasingly competitive environment and global and local brands continue to compete to meet people's needs. This study examines the effect of perceived product quality and price on consumer satisfaction with local fashion products of brand X. This cross-sectional study used a purposive sampling technique. Data were collected offline with an accidental sampling technique using a questionnaire with 182 respondents. The data were processed and analyzed using Microsoft Excel 2021, SPSS 26, and SMART-PLS 3. The results show that there is no relationship between the respondent characteristics and perceived product quality, price, and customer satisfaction. Furthermore, perceived product quality has a positive and significant effect on the perceived price and customer satisfaction. Price perception also has a positive and significant effect on customer satisfaction.